Draft Legislation 222 on Animal Welfare: Challenges and Opportunities for Animal Care in the Laboratory: retos y oportunidades para el cuidado del animal de laboratorio - Cristina (Spei Domus, 2013)
This article reviews the treatment of research with laboratory animals as contained in Draft Legislation 222 of the Colombian Senate. The bill is compared with international norms, such as the iclas guidelines, the ets 123 of the European Union and the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health. Finally, the main limitations of the bill are addressed.